Problems and Solutions on a Protecting Process of Destitute Persons: Comparative Study between Destitute People Homes and Self-Help Settlements - Surasak Wongsa (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2021)
This study aimed to conduct problems and solutions on a protective process of destitute person compared with destitute people homes and self-help settlements. The researcher selected qualitative research method to collect data with focus group discussion technique from 35 key informants such as 12 government officers, 12 government employees, 11 permanent employees, after that we divided into 4 groups (8-9 persons each group). The result showed that there are 3 dimensions on the problems of destitute people protection. The first was the problems of resources such as lack of qualitative and quantitative practitioners, materials, places, and budgets. The second was the problems of protective process such as lack of documents for diagnosis and protection, the discontinuity of protective process, and changing on working context. The third was coordinating problems such as insufficient capability of users, negative attitude to destitute persons. Thus, government should focus on 3 solutions; promoting necessary and important resources such as an allocation of manpower, a procurement of durable article, an adjustment of building and location, coordinating to external organizations for supporting a process of destitute people protection such as requesting treatment history documents and civil registration’s information, and maintaining positive attitude to destitute people such as making public services into community and participating in community’s activities.